Spatial analysis of unimproved drinking water source in East Africa: Using Demographic and Health Survey (DHS) data from 2012–2023 - Lidetu Demoze; Kassaw Chekole Adane; Jember Azanaw; Eyob Akalewold; Tenagne Enawugaw; Mitkie Tigabie; Amensisa Hailu Tesfaye; Gelila Yitageasu (PLoS ONE, 2025)
Background According to the WHO/UNICEF Joint Monitoring Programme, unimproved drinking water sources include unprotected wells and springs, surface water (e.g., rivers, lakes), vendor-provided water, bottled water (without improved alternatives), and tanker truck-provided water. In East Africa, 68.7% of water at very high risk comes from such sources. Using unimproved drinking water sources can lead to serious health risks, including waterborne diseases such as cholera, dysentery, typhoid fever, and hepatitis. Therefore, this study aimed to map the spatial distribution of unimproved drinking water sources in the region. Methods We analyzed recent Demographic and Health Survey (DHS) data from 12 East African countries (Burundi, Comoros, Ethiopia, Kenya, Madagascar, Mozambique, Malawi, Rwanda, Tanzania, Uganda, Zambia, and Zimbabwe). A total of 206,748 households were sampled in 12 East African countries. Data management and analysis were carried out in several stages, beginning with data cleaning, followed by statistical weighting and data merging. This was then followed by geospatial analysis and mapping, and finally, spatial cluster detection. Results Spatial clusters of unimproved drinking water sources were identified within the study area (Global Moran’s I: 0.018, z-score: 87.10, p <  0.05). A total of 167 significant spatial windows containing primary and secondary clusters were identified. The first spatial window contained the primary clusters, while the remaining 166 spatial windows contained secondary clusters. Primary clusters were found in Madagascar and coastal Mozambique, with secondary clusters distributed across all 12 countries analyzed. Conclusions This study identified significant clusters, hotspots, and outliers (high-high clusters) of unimproved drinking water sources across various East African countries. To address these issues effectively, priority should be given to the identified clusters, hotspots, and high-high clusters. Primary recommendations include expanding water treatment facilities, improving water distribution systems, and protecting drinking water sources. Secondary recommendations emphasize strengthening regulations, conducting research, and fostering public-private partnerships to ensure sustainable access to clean water. Finally, we urge collaboration among governments, international organizations, and NGOs to enhance water infrastructure. Their efforts should focus on providing technical assistance, financial support, capacity building, project implementation, advocacy, and financing for drinking water infrastructure in the region. Further research integrating health outcome data with spatial analysis could help identify high-risk regions where the impacts of unimproved water sources are most pronounced.